2017
DOI: 10.3168/jds.2016-12326
|View full text |Cite
|
Sign up to set email alerts
|

Variants in the 3′ untranslated region of the ovine acetyl-coenzyme A acyltransferase 2 gene are associated with dairy traits and exhibit differential allelic expression

Abstract: The acetyl-CoA acyltransferase 2 (ACAA2) gene encodes an enzyme of the thiolase family that is involved in mitochondrial fatty acid elongation and degradation by catalyzing the last step of the respective β-oxidation pathway. The increased energy needs for gluconeogenesis and triglyceride synthesis during lactation are met primarily by increased fatty acid oxidation. Therefore, the ACAA2 enzyme plays an important role in the supply of energy and carbon substrates for lactation and may thus affect milk producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
(77 reference statements)
0
33
0
1
Order By: Relevance
“…In the present work, informative polymorphisms were only observed for the ACAA2 and FASN genes (Tables 1 and 2). Allelic frequencies in the ACAA2 SNP locus were 0.47 and 0.53 for the C and T alleles, respectively, similarly to Orford et al (2012) and Miltiadou et al (2017a), while genotypic frequencies were found to deviate from Hardy-Weinberg equilibrium (online Supplementary Table S3), consistently with our latest study where the frequency of the genotypes carrying the T allele was higher probably due to directional animal selection for increased milk yield (Miltiadou et al, 2017a). In the FASN SNP locus, the respective frequencies for the C and T alleles were 0.67 and 0.33 (online Supplementary Table S3), whereas the C allele frequency reported for the Altamurana and Gentile di Puglia breeds was 0.93 and 1 in Sarda breed (Crisà et al, 2010), suggesting important inter-breed differences.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present work, informative polymorphisms were only observed for the ACAA2 and FASN genes (Tables 1 and 2). Allelic frequencies in the ACAA2 SNP locus were 0.47 and 0.53 for the C and T alleles, respectively, similarly to Orford et al (2012) and Miltiadou et al (2017a), while genotypic frequencies were found to deviate from Hardy-Weinberg equilibrium (online Supplementary Table S3), consistently with our latest study where the frequency of the genotypes carrying the T allele was higher probably due to directional animal selection for increased milk yield (Miltiadou et al, 2017a). In the FASN SNP locus, the respective frequencies for the C and T alleles were 0.67 and 0.33 (online Supplementary Table S3), whereas the C allele frequency reported for the Altamurana and Gentile di Puglia breeds was 0.93 and 1 in Sarda breed (Crisà et al, 2010), suggesting important inter-breed differences.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, the SNP previously associated with milk yield (Orford et al, 2012;Miltiadou et al, 2017a), protein content and fat yield in Chios sheep (Miltiadou et al, 2017a) is also correlated with ω6/ω3 content, an index associated with human health benefits. Similarly to Miltiadou et al (2017a), fat percentage was not affected by the identified ACAA2 polymorphism.…”
Section: Resultsmentioning
confidence: 97%
“…Several previous studies have shown that 3 UTR variants can affect gene transcription [49,50], and structural changes in the 3 UTR region are closely related to livestock and poultry production performance [51][52][53]. The 3 UTR is generally thought to regulate gene expression by affecting the stability of mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis found that among the 21 proteins quanti ed, ten proteins that regulate fat deposition have major variations in expression between leg muscles and breast muscles. For example, Acetyl CoA Acyltransferase 2 (AcetylCoAacyltransferase 2, ACAA2) is a key enzyme for fatty acid oxidation, widely distributed in mammalian and bird tissues and cytoplasm, and plays a vital role in the metabolism of fatty acids (Sodhi et al 2014), and regulates intermuscular fat content (Miltiadou et al 2017). Hence, this gene is considered a candidate for detecting intermuscular fat content (Miltiadou et al 2017).…”
Section: Discussionmentioning
confidence: 99%